KONTRIBUSI USAHATANI KOPRA TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI DESA TATARANDANG KECAMATAN BULAGI SELATAN KABUPATEN BANGGAI KEPULAUAN - Goligitan, Netria; Zaenuddin, Ruslan A; Masese, Zaedar. A. Dg.; Masese, Risa Apriyana A. Dg. (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2025)
Copra farming is one of the main sources of income for coconut farming households in the archipelago. This study aims to analyze the contribution of copra farming to household income and its economic feasibility in Tatarandang Village, South Bulagi District, Banggai Islands Regency. The study was conducted from June to August 2025. The study population was all 140 coconut farmers. The sample size was determined using the Slovin formula with a 15% error rate, resulting in 34 respondents, selected purposively. Data analysis includes analysis of costs, revenues, income, income contributions, and business feasibility using the R/C Ratio. The results showed that the average income of copra farming was Rp21,463,000 with a total production cost of Rp2,929,933, resulting in a net income of Rp18,533,067 per harvest season. The total income of farmer households was Rp21,751,008 per four months, with the contribution of copra farming reaching 85.21%. The R/C Ratio value of 7.32 (>1) indicates that copra farming is feasible and profitable and is the main supporter of the economy of farmer households in Tatarandang Village.